2012
DOI: 10.1039/c1sm06964k
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite silicasurfactant microcapsules by evaporation induced self assembly: tuning the morphological buckling by modifying viscosity and surface charge

Abstract: Nanocomposite microcapsules of silica and surfactants have been synthesized using evaporation induced self-assembly through spray drying. It was established using electron microscopy and smallangle neutron/X-ray scattering experiments that the viscosity of the virgin dispersion and surface charge of colloidal components play a significant role in the buckling of spray droplets during drying. Hollow spherical grains are realized at relatively low viscosity and higher surface charge while mushroom like grains ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 37 publications
0
54
0
Order By: Relevance
“…56,57 As the water evaporates, capillary forces compress the shell; consequently, the nanosheet shell yields and buckles due to strong compression forces, in accordance with elastic shell deformation theory. 33,61 Depending on the moduli of the shell itself, dimpled structures form as the interior volume is reduced. 29,59,60 Again this process, particularly the balance between convective and diffusive mass transfer, is discussed in detail in the previous report.…”
Section: Pccp Papermentioning
confidence: 99%
“…56,57 As the water evaporates, capillary forces compress the shell; consequently, the nanosheet shell yields and buckles due to strong compression forces, in accordance with elastic shell deformation theory. 33,61 Depending on the moduli of the shell itself, dimpled structures form as the interior volume is reduced. 29,59,60 Again this process, particularly the balance between convective and diffusive mass transfer, is discussed in detail in the previous report.…”
Section: Pccp Papermentioning
confidence: 99%
“…This indeed indicates the significant role of inter-particle interaction in morphological transformation. It should be mentioned that in some of the previous works [24][25]27,[29][30][31][47][48][49][50][51][52][53][54], using single-component colloidal suspension, it was indicated that the spherical shape of droplet is retained even in the granule because of isotropic drying at slow drying rate. It has also been discussed that the formation doughnut shape is a consequence of anisotropic drying and shell buckling when drying rate is fast enough.…”
Section: Resultsmentioning
confidence: 95%
“…These include spray drying [3], freeze-drying [4], porogenation [5,6], micro-emulsion formation [7], gas-blowing techniques [8], phase separation [9] etc. Synthesis of micro-granules through drying of suspension-droplets is a well established process that can produce micrometric composite granules in a single step through evaporation-induced assembly [10][11][12][13][14][15]. Such assembly process is a quick and efficient bottom-up approach for realizing multi-functional composite micro-granules.…”
Section: Introductionmentioning
confidence: 99%